2018
DOI: 10.1017/s0142716418000644
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency in relation to reading ability in students with and without dyslexia

Abstract: Verbal fluency tasks, in which participants generate words during a set time, have been used in research and assessments of neurobiological disorders and impairments. Research on verbal fluency in dyslexia has shown impaired performance in semantic and letter fluency. However, studies report inconsistent results, and action fluency has not been examined in dyslexia. Current research has mainly examined verbal fluency in relation to executive functions, vocabulary, and phonological processing. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 101 publications
(192 reference statements)
0
4
0
1
Order By: Relevance
“…Verbal fluency is commonly assessed in relation to dyslexia and a recent research study suggests potential links between verbal fluency and reading abilities in dyslexic individuals. 26 Fawcett and Nicolson 7 state that it might be possible for a child to be weak in the 'Verbal Fluency' subtest but moderately good in the 'Semantic Fluency' subtest, which seems to be confirmed with this child. As dyslexic individuals have usually no serious issues with reasoning abilities, it is important to identify the shortcomings, such as further testing.…”
Section: Discussionmentioning
confidence: 58%
“…Verbal fluency is commonly assessed in relation to dyslexia and a recent research study suggests potential links between verbal fluency and reading abilities in dyslexic individuals. 26 Fawcett and Nicolson 7 state that it might be possible for a child to be weak in the 'Verbal Fluency' subtest but moderately good in the 'Semantic Fluency' subtest, which seems to be confirmed with this child. As dyslexic individuals have usually no serious issues with reasoning abilities, it is important to identify the shortcomings, such as further testing.…”
Section: Discussionmentioning
confidence: 58%
“…Particular difficulties with the efficient and flexible access of declarative information that had successfully been stored in long-term memory came out in several interviews. These problems in accessing information are very suggestive of the difficulties with verbal fluency that have been documented under experimental conditions in adults with dyslexia (e.g., [30,[88][89][90][91]). The participants in the current study reported slower, more effortful, and reduced access to information in long-term memory, all hallmarks of reduced verbal fluency (e.g., [92][93][94]).…”
Section: Discussionmentioning
confidence: 76%
“…ise 16'sı disleksi tanısı almış 26'sı tipik gelişim gösteren 42 üniversite öğrencisi ile gerçekleştirdiği çalışmada; yönetici işlevler, kelime bilgisi ve fonolojik işleme becerileri ile sözel akıcılık becerileri arasındaki ilişkiyi incelemiştir. 32 Sözel akıcılık becerilerini semantik, akıcılık ve eylem akıcılığı olmak üzere 3 farklı biçimde ele almıştır. Çalışma sonuçları fonolojik farkındalığın semantik akıcılık ve eylem akıcılığı ile önemli ölçüde ilişkili olduğunu göstermiştir.…”
Section: Kısa Süreli Bellek çAlışma Belleği Fonolojik Farkındalık Din...unclassified